2017
DOI: 10.1021/jacs.7b03141
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Nature of Anomalously Fast Energy Storage in T-Nb2O5

Abstract: While T-NbO has been frequently reported to display an exceptionally fast rate of Li-ion storage (similar to a capacitor), the detailed mechanism of the energy storage process is yet to be unraveled. Here we report our findings in probing the nature of the ultrafast Li-ion storage in T-NbO using both experimental and computational approaches. Experimentally, we used in operando Raman spectroscopy performed on a well-designed model cell to systematically characterize the dynamic evolution of vibrational band gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
177
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(185 citation statements)
references
References 79 publications
7
177
0
1
Order By: Relevance
“…[20,21] 2) The enhanced ionicity of NbO bond: as theoretically predicted by the previous work, the enhanced ionicity of NbO bond with the existence of [PO 4 ] 3− group in the present 2NbOPO 4 ·H 3 PO 4 ·H 2 O crystal can efficiently produce a high operating voltage window up to 1.0 V. [16][17][18][19] 3) The outstanding structure stability of the layered 2NbOPO 4 ·H 3 PO 4 ·H 2 O ensure the long-term charge/ discharge cycling stability. However, our NPene sheets can greatly utilizes the bulk of electrode material in charge storage through fast intercalation of cations (H + or Li + ), resulting in a high specific capacitance and energy density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] 2) The enhanced ionicity of NbO bond: as theoretically predicted by the previous work, the enhanced ionicity of NbO bond with the existence of [PO 4 ] 3− group in the present 2NbOPO 4 ·H 3 PO 4 ·H 2 O crystal can efficiently produce a high operating voltage window up to 1.0 V. [16][17][18][19] 3) The outstanding structure stability of the layered 2NbOPO 4 ·H 3 PO 4 ·H 2 O ensure the long-term charge/ discharge cycling stability. However, our NPene sheets can greatly utilizes the bulk of electrode material in charge storage through fast intercalation of cations (H + or Li + ), resulting in a high specific capacitance and energy density.…”
Section: Resultsmentioning
confidence: 99%
“…[15] More importantly, it has been theoretically predicted a much higher potential (≈1.0 V in aqueous electrolyte) in layered phosphates than in most of the traditional pseudocapacitive materials due to the enhanced iconicity of metaloxygen bond with the existence of [PO 4 ] 3− group. [20,21] Especially, the pseudocapacitance occurs in the T-Nb 2 O 5 bulk rather than the surface or near-surface of the electrode, resulting high specific capacitances and energy density. A unique Li + -intercalation pseudocapacitance has been found in T-Nb 2 O 5 (40 µm thick) electrode, which holds a great perspective on the development of electrochemical electrodes.…”
mentioning
confidence: 99%
“…The carbon content of the composites was varied between 0 and 16 wt% by changing the Nb 2 O 5 /TPB ratio, which was achieved by removing the desired amount of TPB with acetone. [48][49][50][51][52][53] They are dominated by the intense band (at 693 cm −1 ) arising from the symmetrical TO stretch of NbO bonds in the low distorted corner-or edgesharing bipyramidal units of the oxide lattice; [48,50,52] weaker bands are further detected at 122, 227, 308, 465, and 809 cm −1 . Small carbonencapsulated Nb 2 O 5 NCs (NP-X where X is the carbon content samples) were synthesized by reaction of NbCl 5 with acetophenone ( Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the Nb‐ions are surrounded by either six or seven O‐ions, which constitutes the edge/corner‐sharing distorted NbO 6 and NbO 7 polyhedra . According to the atomic arrangement of T‐Nb 2 O 5 , its crystal structure can be regarded as two alternating atomic layers, including the loosely packed 4g layer and the denser 4h layer ( Figure a) . Owing to the capacious atomic accommodation space, the 4g layer provides preferential storage and transport sites for Li‐ions.…”
Section: Nb2o5 Electrodesmentioning
confidence: 99%
“…Moreover, the calculated energy migration barriers for Li‐ions through Path A or Path B are ranged from 0.25 to 0.33 eV, further confirming the structural merit of T‐Nb 2 O 5 for superior Li‐ion transport character. These two Li‐ion diffusion paths are both within the 4g layer, resulting in the formation of a quasi‐2D network for Li‐ion transport …”
Section: Nb2o5 Electrodesmentioning
confidence: 99%